Postradiation lower motor neuron syndrome presenting as monomelic amyotrophy. Issue 7 (July 1991) - Lamy, C; Mas, J L; Varet, B; Ziegler, M; de Recondo, J
Abstract : Monomelic amyotrophy developed 16 months, nine and 12 years after irradiation of the lumbosacral spinal cord for seminoma in one patient and for Hodgkin's disease in two others. In two patients, involvement was clinically limited to one leg, with a subacute course followed by plateau in the first case and with progressive worsening in the second one. In the third patient, the course was progressive with involvement of the other lower limb occurring five years later. From clinical and electrophysiological data, it seems probable that the disease process was a result of a selective injury to the lower motor neuron in the lower spinal cord.